Sustainable furniture design: an alternative approach to enhance learning process in autism classroom / Nurhikma Mat Yusof, Rosaliana Rahim and Ridzuan Adli Azidin - Mat Yusof, Nurhikma; Rahim, Rosaliana; Azidin, Ridzuan Adli (2016)
In this research, researcher chooses an autism classroom as the case study. Researchers are interested to study about the effectiveness of sustainable furniture design that might contribute the behavior development of learning process for the autism kids. The objectives of The National Autism Society of Malaysia (NASOM) is to advocate for the rights of the autistic people and in doing so provide oppounities for them to learn and lead a productive and fulfilling life. Autism classroom is a place where these autism kids will learn to develop skills and knowledge in order to live independently in the future. They are not being scared of danger, either being too sensitive or not sensitive at all to pain, avoiding eye contact, has difficulty expressing what they want or need, routine has to always be the same, and may show an overall difficulty interacting with others. Incorporate with the sustainable furniture design, natural material and function built in, results oriented and emphasis is on the acquisition of skills and changes in behavior. For that reason, researchers are highly interested in investigating the effectiveness of the sustainable furniture in classroom towards behavior of learning in developing independent autism people for them to sustain with normal people in community.